2002
DOI: 10.1007/s00056-002-0067-8
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Elasticity Parameters of the Human Periodontal Ligament and the Location of the Center of Resistance of Single-rooted Teeth

Abstract: The elasticity parameters were found to be on a similar scale to those determined in previous studies on multi-rooted pig teeth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(72 citation statements)
references
References 25 publications
1
62
0
9
Order By: Relevance
“…In the finite element model, teeth, alveolar bones, brackets, periodontal spaces, C-implant, and archwire were constructed with fine tetrahedron solid elements; the tooth and bracket were connected without interference, and each tooth contacted the next at the contact point as individual elements (Fig 2, D). In this study, teeth, alveolar bones, and periodontal spaces were assumed to be isoparametric and homogeneous linear elastic bodies, and the material properties of the elements were Young's modulus and Poisson's ratio according to the studies of Tanne et al, 28 Ziegler et al, 29 and Poppe et al 30 (Table I). In the system studies, we construct the x-axis as the in-out direction, the y-axis as the labiolingual direction, and the z-axis as the upper-lower direction, and defined 1x as the left central incisor direction, 1y as the labial direction, 1z as the apical direction, and the x-y plane as the occlusal plane of the teeth (Fig 3, A and B).…”
Section: Methodsmentioning
confidence: 99%
“…In the finite element model, teeth, alveolar bones, brackets, periodontal spaces, C-implant, and archwire were constructed with fine tetrahedron solid elements; the tooth and bracket were connected without interference, and each tooth contacted the next at the contact point as individual elements (Fig 2, D). In this study, teeth, alveolar bones, and periodontal spaces were assumed to be isoparametric and homogeneous linear elastic bodies, and the material properties of the elements were Young's modulus and Poisson's ratio according to the studies of Tanne et al, 28 Ziegler et al, 29 and Poppe et al 30 (Table I). In the system studies, we construct the x-axis as the in-out direction, the y-axis as the labiolingual direction, and the z-axis as the upper-lower direction, and defined 1x as the left central incisor direction, 1y as the labial direction, 1z as the apical direction, and the x-y plane as the occlusal plane of the teeth (Fig 3, A and B).…”
Section: Methodsmentioning
confidence: 99%
“…The modulus of elasticity (E) and Poisson's ratio (µ) of each tissue were referred from previous studies 7,[12][13][14][15][16] and are shown in Table 1. Nine combination groups of different bilinear elastic moduli of the PDL for each phase (E1 and E2) were assumed for comparison (M1-M9, Table 2).…”
Section: Materials Propertiesmentioning
confidence: 99%
“…Nine combination groups of different bilinear elastic moduli of the PDL for each phase (E1 and E2) were assumed for comparison (M1-M9, Table 2). Values of E1 and E2 which were to be investigated were proposed on the basis of earlier papers 7,8,12,13) . In these papers E1 and E2 ranged from 0.05 MPa to 0.…”
Section: Materials Propertiesmentioning
confidence: 99%
See 2 more Smart Citations